2005
DOI: 10.1021/jp0534582
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Structure of the Hydrated Proton:  A Comparative X-ray Absorption Study of Aqueous HCl and NaCl Solutions

Abstract: The oxygen K edge X-ray absorption spectra of aqueous HCl and NaCl solutions reveal distinct perturbations of the local water molecules by the respective solutes. While the addition of NaCl leads to large spectral changes, the effect of HCl on the observed X-ray absorption spectrum is surprisingly small. Density functional theory calculations suggest that this difference primarily reflects a strong blue shift of the hydrated proton (in either the Eigen (H 9 O 4 + ) or Zundel (H 2 O 5 + ) forms) spectrum relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 33 publications
5
60
3
Order By: Relevance
“…It is not universally agreed upon whether the Cl -ion itself imparts any specific changes to the features of the XAS of different solutions. 18,35,36 Our own dynamics calculations indicate that the first solvation shell of Cl -, identified by water molecules with one or more hydrogen oriented toward the anion, is floppy with rapid exchange events. The average coordination number is 5.7, and the overall distribution, primarily with coordination numbers between 4 and 7, is broad ( Figure 2).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…It is not universally agreed upon whether the Cl -ion itself imparts any specific changes to the features of the XAS of different solutions. 18,35,36 Our own dynamics calculations indicate that the first solvation shell of Cl -, identified by water molecules with one or more hydrogen oriented toward the anion, is floppy with rapid exchange events. The average coordination number is 5.7, and the overall distribution, primarily with coordination numbers between 4 and 7, is broad ( Figure 2).…”
Section: Resultsmentioning
confidence: 88%
“…Nevertheless, earlier results, also from Cappa et al, compared 4 M HCl and NaCl solutions and found the HCl spectrum to be very similar to that for bulk water and dissimilar from that of NaCl. 36 The authors suggested that the effects of H + and Cl -roughly counteracted each other, yielding spectroscopic features very much like those of bulk water. However, other studies have suggested 35 that the cations contribute more significantly to the features of the X-ray absorption spectrum because they more directly interact with the oxygens of water.…”
Section: Figurementioning
confidence: 99%
“…16,21,22 As a starting point, XA spectra of the bare OH -ion and of a free H 2 O molecule have been calculated ( Figure 2); the influence of solvation environment will be discussed shortly. These calculations indicate that the bare OH -ion absorbs at lower energies than do free H 2 O molecules, consistent with the experimental observations for the aqueous solutions.…”
Section: Discussionmentioning
confidence: 99%
“…3,[9][10][11][12] The details, such as the depth profile of ion concentrations, depend very much on the molecular model and interaction potentials assumed. [9][10][11][12] Experiments carried out with scanning tunneling microscopy (STM) 13 , X-ray spectroscopy 14,15 , and attenuated total reflection (ATR) 8 have been used to verify the theoretical prediction. They however suffer from either the water surface being too dynamic or the techniques not being sufficiently surface-specific.…”
Section: Introductionmentioning
confidence: 99%